So long a toilet! Deviations from a conventional design, level of latrine construction and use by rural households in Nyanga district, Zimbabwe - Simbi, S.; Kanda, A. (BMC Public Health, 2025)
Background Building toilets and getting people to use them is critical for public health. When prescribed with a sanitation option, households may go with it, choose alternatives, construct its non-conventional designs or practise open defaecation. Non-conventional designs may compromise operational efficiency and safety. This study assessed the construction and use of the Blair ventilated improved pit (BVIP) latrine, a sanitation option of choice for rural Zimbabwe, southern Africa. Methods A semi-structured questionnaire was administered to 191 rural households who own BVIP latrines or their upgradable designs in a cross-sectional study in 2022. Latrine characteristics were physically observed using a checklist. Households were selected from nine villages of Nyanga district, Zimbabwe. The association between socioeconomic demography and level of latrine construction were evaluated using Chi square test. Cross tabulations were used to show the level of latrine construction and design. Binary logistic regression was used to determine significant predictors of latrine construction. Statistical relationships were considered significant if p ≤ 0.05. Key findings Households self-reported adopting the BVIP latrine mainly due to government encouragement (42.07%) and for social reasons (34.49%) than for perceived health and hygiene benefits (4.71%). Some built latrines had wall openings, lacked roofs, vent pipes with fly screens and handwashing facilities. Latrine construction was significantly associated with household size, monthly income, number of cattle owned, latrine financier and the presence of a resident formally employed household member (p < 0.001). Some household members did not use latrines (40.84%) citing main reasons as unhygienic environment (39.75%), inconveniences (26.92%) and foul smell (17.95%). Increasing household size, income and the number of cattle, the presence of a resident formally employed household member and NGO financing latrine construction were more likely to complete (p < 0.05). Conclusions Ongoing sanitation developments (outside specific interventions) need close monitoring for latrine construction and dissemination of sanitation behaviour change messages at a local scale. The mantra, so long a toilet, does not work when a conventional latrine design is prescribed. Keywords BVIP latrine design, Conventional design, Rural sanitation, Sanitation option, Zimbabwe
Keywords: Rural sanitation; Blair Ventilated Improved Pit latrines; Latrine design; Sanitation options